The Impact of Greenwashing on Perceived Environmental Performance Toward Brand Avoidance and Brand Switching - Ibau, Silviana; Kholid Mawardi, Mukhammad; Rahimah, Anni (FIA UB, 2025)
This study uses a case study of Le Minerale gallon users to examine how greenwashing affects perceived environmental performance, brand avoidance, and brand switching.